An acid-responsive bivalent iron nanoreactor, a preparation method and application thereof

CN122998099APending Publication Date: 2026-10-30SHANDONG RES INST OF TUMOUR PREVENTION TREATMENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611470409.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有相关材料通常将二氧化硅主要作为相对惰性的载体,或者仅利用铁的Fenton反应活性,较少同时发挥含铁骨架的酸响应降解功能、Fe2+/Fe3+不同价态的功能差异以及铁源与卟啉配体的同步释放作用

Benefits of technology

(1)SiOFe含铁骨架在生理中性环境下可以约束铁物种,抑制铁提前泄漏;到达肿瘤弱酸性环境(pH5.56.5)时骨架发生降解,骨架本身同时充当结构支撑、可降解单元与双价态铁(Fe2+、Fe3+)储库,解决了游离铁提前泄露、非特异性结合的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998099A_ABST
    Figure CN122998099A_ABST
Patent Text Reader

Abstract

The application discloses an acid-responsive bivalent iron nano-reactor as well as a preparation method and application thereof, and belongs to the technical field of biological medicines. The nano-reactor comprises Fe-doped hollow mesoporous silica, a surface polyethylene glycol layer and protoporphyrin IX loaded in the hollow cavity and the mesopores, wherein Fe 2+ and Fe 3+ constitute a part of a skeleton through Si-O-Fe bonds. The skeleton limits the release of iron species and protoporphyrin IX under neutral conditions; the skeleton is degraded and the release of both is promoted under the condition of pH 5.5-6.5, forming a Fe-protoporphyrin IX-like coordination structure with photothermal response; mild heating generated by 658 nm light irradiation can promote the Fenton reaction mediated by iron. The acid-triggered co-release, local coordination assembly and photothermal-enhanced chemical kinetics are integrated in the same nano-platform, and the application can be used for preparing tumor treatment drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical technology, specifically relating to an acid-responsive divalent iron nanoreactor, its preparation method, and its application. Background Technology

[0002] Chemokinetic therapy utilizes hydrogen peroxide in the tumor microenvironment to generate hydroxyl radicals in situ via Fenton or Fenton-like reactions, thereby increasing oxidative stress within tumor cells. Compared to continuously released cytotoxic drugs, this treatment approach can achieve a certain degree of local activation by leveraging the relatively high hydrogen peroxide levels, weak acidity, and abnormal reducing homeostasis in the tumor region.

[0003] Iron species are commonly used reactive components in Fenton reactions, but free iron ions may leak prematurely, be oxidized, or non-specifically bind to biomolecules such as proteins during systemic circulation, resulting in reduced effective iron reaching tumor sites and increasing the risk of unintended oxidation reactions in normal tissues. Immobilizing or encapsulating iron in nanocarriers can improve stability, but if the binding of iron to the carrier is too strong, it may limit effective release under acidic conditions.

[0004] Protoporphyrin IX possesses tetrapyrrole coordination cavities and red light absorption properties, enabling it to form iron porphyrin structures with specific photophysical properties. However, pre-prepared iron porphyrins often suffer from hydrophobic aggregation, insufficient water dispersibility, and limited colloidal stability in blood. Separate delivery of the iron source and protoporphyrin IX may also affect coordination assembly due to inconsistencies in their arrival time and local concentrations.

[0005] Hollow mesoporous silica possesses a large internal space and tunable channels, enabling the loading of porphyrin molecules. Existing related materials typically utilize silica primarily as a relatively inert support, or solely leverage the Fenton reactivity of iron, rarely simultaneously utilizing the acid-responsive degradation function of the iron-containing framework and Fe... 2+ / Fe 3+ Functional differences between different valence states and the synchronous release of iron source and porphyrin ligand.

[0006] Fe 2+ It can directly react with hydrogen peroxide to produce hydroxyl radicals, Fe 3+ It can then participate in valence cycling and coordinate with pyrrole nitrogen in porphyrin. If Fe is stored within the same nanostructure... 2+ Fe 3+ The co-release of Fe, along with protoporphyrin IX and triggered by an acidic microenvironment, holds promise for enhancing Fe production. 2+ The enriched species mainly undertake Fenton catalysis, enabling another portion of iron to form a photoresponsive coordination structure with protoporphyrin IX locally, thereby further promoting the Fenton reaction by utilizing photothermal heating.

[0007] Therefore, there is a need for a nanoreactor that remains relatively stable under neutral conditions, degrades under weakly acidic conditions, and can co-release iron species and protoporphyrin IX from the framework, in order to reduce premature leakage and pre-formed iron porphyrin aggregation, while achieving local coordination assembly and photothermal enhancement of chemical kinetics. Summary of the Invention

[0008] In view of this, the purpose of this invention is to address the problems existing in the prior art by providing an acid-responsive divalent iron nanoreactor, its preparation method, and its application; this acid-responsive divalent iron nanoreactor enables Fe-containing... 2+ and Fe 3+ The Si-O-Fe framework combines structural support, acid-responsive degradation, and iron source storage functions. It also utilizes a hollow mesoporous structure to co-load protoporphyrin IX, thereby achieving the synchronous release and local coordination assembly of iron species and protoporphyrin IX in an acidic environment.

[0009] To achieve the above objectives, the technical solution of the present invention is as follows: One objective of this invention is to provide an acid-responsive bivalent iron nanoreactor, comprising Fe-doped hollow mesoporous silica nanoparticles, a polyethylene glycol layer disposed on the surface of the nanoparticles, and protoporphyrin IX supported in the hollow cavity and / or mesopores; wherein the Fe is Fe 2+ and Fe 3+ They coexist and form part of the nanoparticle framework through Si-O-Fe bonds; the nanoreactor undergoes framework degradation under pH 5.5–6.5 conditions and co-releases iron species and protoporphyrin IX to form a Fe-protoporphyrin IX-like coordination structure.

[0010] In some embodiments, the Fe-doped hollow mesoporous silica nanoparticles have an average hydrated particle size of 202.52 nm, an average mesopore size of 9.551 nm, and a specific surface area of ​​65.042 m². 2 ·g -1 The pore volume is 0.435 cm³. 3 ·g -1 The Fe 2+ and Fe 3+ The relative contents were 44.17% and 55.83%, respectively, and the encapsulation efficiency of the protoporphyrin IX was 52.52%.

[0011] A second objective of this invention is to provide a method for preparing an acid-responsive divalent iron nanoreactor, comprising the following steps: Using silica nanospheres as sacrificial templates, a hydrothermal dissolution-regeneration reaction was carried out in the presence of iron acetylacetone and urea to obtain Fe-doped hollow mesoporous silica nanoparticles; the nanoparticles were then surface-modified with methoxy polyethylene glycol silane; and the surface-modified nanoparticles were incubated with protoporphyrin IX in ethanol in the dark to load protoporphyrin IX into the hollow cavity and / or mesopores.

[0012] In some embodiments, the hydrothermal dissolution-regeneration reaction in the preparation method includes: dispersing 12.5 mg of silica nanospheres in 3.75 mL of deionized water, adding 88 mg of ferric acetylacetone, 1200 mg of urea and 2.5 mL of ethanol, and reacting at 200 °C for 24 h.

[0013] In some embodiments, the surface modification in the preparation method includes reacting 80 mg of Fe-doped hollow mesoporous silica nanoparticles with 50 mg of methoxy polyethylene glycol silane in anhydrous ethanol at 78 °C for 24 h; the protoporphyrin IX loading includes stirring 20 mg of surface-modified nanoparticles with 15 mg of protoporphyrin IX in 25 mL of ethanol in the dark for 12 h.

[0014] A third objective of this invention is to provide a pharmaceutical composition comprising the above-mentioned acid-responsive divalent iron nanoreactor and a pharmaceutically acceptable aqueous carrier, wherein the aqueous carrier is a sterile phosphate buffer or physiological saline.

[0015] The fourth objective of this invention is to provide the application of the above-mentioned acid-responsive bivalent iron nanoreactor in the preparation of drugs for tumor chemokinetics and photothermal enhancement therapy, wherein the drugs are suitable for use under 658 nm illumination.

[0016] The beneficial effects of this invention are: (1) The SiOFe iron-containing framework can constrain iron species and inhibit premature iron leakage under physiologically neutral conditions; when it reaches the weakly acidic environment of the tumor (pH 5.5-6.5), the framework degrades, and the framework itself simultaneously acts as a structural support, a degradable unit, and a source of divalent iron (Fe). 2+ Fe 3+ The storage facility solves the problems of premature leakage and non-specific binding of free iron.

[0017] (2) Using a hollow mesoporous silica carrier, the iron source and protoporphyrin IX are co-located in the same nanoreactor. Under acidic conditions, the iron species and protoporphyrin IX are released synchronously in the same time window, generating Fe protoporphyrin IX-like coordination structures in situ at the tumor site. This avoids the defects of hydrophobic aggregation, poor colloidal stability, and low coordination efficiency caused by the pre-synthesized iron porphyrin.

[0018] (3) The different valence states of iron within the system have clearly defined functional divisions. 2+ It mainly mediates the Fenton reaction to generate hydroxyl radicals to achieve chemokinetic therapy; the in-situ generated Fe protoporphyrin IX-like structure has a 658nm photothermal effect, and the photothermal heating further amplifies the oxidative damage of the Fenton reaction, effectively realizing the photothermal-enhanced chemokinetic antitumor effect.

[0019] (4) Polyethylene glycol modification on the surface of nanoparticles can effectively improve the water dispersibility of the material and facilitate in vivo delivery.

[0020] (5) At the cellular level, it can induce tumor cells to produce reactive oxygen species, mitochondrial damage, and ferroptosis-related oxidative damage; in animal experiments, it can significantly inhibit tumor growth, with a tumor growth inhibition rate of up to 72.5%; under experimental drug administration conditions, there is no significant damage to the major organs, blood, and liver and kidney functions of mice, and it has good short-term biological tolerance.

[0021] (6) The present invention employs sol-gel, hydrothermal dissolution and regrowth, silane modification and physical loading processes. The raw materials are readily available, have good repeatability, and facilitate subsequent scale-up production and formulation development. Attached Figure Description

[0022] Figure 1 A schematic diagram illustrating the construction and mechanism of action of an acid-responsive divalent iron nanoreactor; Figure 2 The images show the fabrication process and structural characterization results of the nanoreactors. Specifically: a: Scanning electron microscope image of silica nanospheres; b: Schematic diagram of hydrothermal dissolution-regeneration preparation of DHU-FS; c: Transmission electron microscope image of DHU-FS; d: High-angle annular dark-field scanning transmission electron microscope image of DHU-FS and elemental distribution maps of O, Si, and Fe; e: High-resolution X-ray photoelectron spectroscopy (HPS) of Fe 2p in DHU-FS and Fe... 2+ / Fe3 + Peak fitting results; f: Fourier transform infrared spectra of SiO2, DHU-FS, polyethylene glycol silane and DHU-FSP; g: UV-Vis absorption spectra of DHU-FS, DHU-FSP, protoporphyrin IX and DHU-FSPP.

[0023] Figure 3The results show the acid-responsive degradation of the skeleton, the release of iron / protoporphyrin IX, and the characterization of local coordination. Among them, a: transmission electron microscopy images of DHU-FSPP after incubation at different pH conditions for 6 h or 60 h; b and c: cumulative release curves of iron and protoporphyrin IX under different pH conditions, respectively; d: transmission electron microscopy images of DHU-FSPP before and after degradation at pH 5.5; e and f: UV-Vis absorption and fluorescence spectra after acid incubation, respectively; g: Raman spectra of DHU-FS, DHU-FSPP, acid-incubated DHU-FSPP, and independently prepared Fe-protoporphyrin IX samples; h: N 1s high-resolution X-ray photoelectron spectroscopy of the acid-incubated product.

[0024] Figure 4 The results show the Fenton activity, photothermal properties, and photothermally enhanced Fenton reaction. Specifically, a: UV-Vis absorption spectra of methylene blue under different reaction combinations; b and c: methylene blue fading results at different pH and DHU-FSPP concentrations, respectively; d: electron spin resonance signal related to hydroxyl radicals; e and f: Fe-protoporphyrin IX sample and Fe... 2+ Fenton activity comparison; g: heating curves of Fe-protoporphyrin IX samples at different concentrations; hj: heating curves at different pH, different light power densities and different DHU-FSPP concentrations, respectively; k: repeated heating-cooling cycle curves; l: tetramethylbenzidine oxidation results with and without 658 nm light irradiation.

[0025] Figure 5 The results show the effects of cell uptake, changes in intracellular structure, and light-induced cell damage. Among them, a: uptake of Cy5.5-labeled DHU-FSPP in 4T1 cells and its colocalization with lysosomes; b: linear scan results of Cy5.5 and lysosomal fluorescence signals; c: transmission electron microscopy images of ultrathin sections of 4T1 cells and L929 cells; d: live / dead staining images of 4T1 cells in different treatment groups; e: quantitative results of live and dead cells.

[0026] Figure 6 The results show the oxidative stress, mitochondrial function, and ferroptosis-related indicators in 4T1 cells after DHU-FSPP treatment; where a: intracellular reactive oxygen species fluorescence image; b: JC-1 mitochondrial membrane potential staining image; c and d: GPX4 immunofluorescence and quantitative results, respectively; e: intracellular GSH / GSSG ratio.

[0027] Figure 7The results show the photothermal response, tumor-suppressing effect, and histological findings in 4T1 tumor-bearing mice. Specifically, a: drug administration and light treatment process; b: mouse weight changes during treatment; c: infrared thermography of the tumor during 658 nm light irradiation; d: in vitro tumor images after treatment; e: Western blotting results of HSP70, SLC7A11, and GPX4 proteins in the tumor tissue; f: hematoxylin-eosin staining, GPX4 immunohistochemical staining, and TUNEL staining results of the tumor tissue. Detailed Implementation

[0028] The present invention will be further described below through specific embodiments, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not depart from the basic idea of ​​the present invention, they are all within the protection scope of the present invention.

[0029] In the following examples, reagents not specifically mentioned can be used directly, and the water is deionized water.

[0030] For ease of description, this paper designates Fe-doped hollow mesoporous silica as DHU-FS, the polyethylene glycol-modified material as DHU-FSP, and the acid-responsive bivalent iron nanoreactor further loaded with protoporphyrin IX as DHU-FSPP. The term "co-release" in this paper refers to the release of both iron species and protoporphyrin IX within the same acidic incubation conditions and time window, without requiring identical release rates or a fixed molar ratio. The term "Fe-protoporphyrin IX-like coordination structure" refers to a coordination product whose morphology and various spectral characteristics are consistent with or similar to those of an independently prepared Fe-protoporphyrin IX control, without limiting it to a single composition, a single iron valence state, or a pure compound with a defined coordination number.

[0031] like Figure 1 As shown, this invention uses Fe-doped hollow mesoporous silica as the core structure: the Si-O-Fe framework simultaneously provides acid-responsive structural units and Fe... 2+ / Fe 3+ The reservoir, hollow cavity, and mesopores are used to load protoporphyrin IX, and the surface polyethylene glycol layer is used to improve water dispersibility. The material remains relatively stable at pH 7.4, but the framework degrades and promotes the co-release of iron species and protoporphyrin IX at pH 5.5–6.5; the released components form a photothermally responsive Fe-protoporphyrin IX-like coordination structure. 2+ Enriched species mediate the Fenton reaction, and photothermal heating further promotes the iron-mediated oxidation reaction.

[0032] Example 1 (1) Preparation of silica nanospheres 0.5 mL of tetraethyl orthosilicate was added to 50 mL of anhydrous ethanol and ultrasonically dispersed. Separately, 4 mL of deionized water and 4 mL of ammonia solution (25%–28% by mass) were added to 50 mL of anhydrous ethanol and mixed thoroughly. The two solutions were combined and ultrasonically reacted at room temperature for 3 h. The white precipitate was collected by centrifugation at 10000 rpm for 5 min, washed three times with ethanol and deionized water respectively, and redispersed in deionized water. The average hydrated particle size of the obtained silica nanospheres was 111.6 nm.

[0033] (2) Preparation of Fe-doped hollow mesoporous silica 12.5 mg of the silica nanospheres obtained in Example 1 were dispersed in 3.75 mL of deionized water, and 88 mg of ferric acetylacetone, 1200 mg of urea, and 2.5 mL of ethanol were added. After ultrasonic mixing, the mixture was transferred to a hydrothermal reactor and reacted at 200 °C for 24 h. After cooling to room temperature, the mixture was centrifuged at 10000 rpm for 5 min and washed three times with ethanol and deionized water, respectively, to obtain Fe-doped hollow mesoporous silica nanoparticles.

[0034] (3) Polyethylene glycol modification and protoporphyrin IX loading 80 mg of the nanoparticles obtained in Example 2 were dispersed in anhydrous ethanol, and 50 mg of methoxy polyethylene glycol silane was added. The mixture was reacted at 78 °C for 24 h. The product was collected by centrifugation, washed three times with ethanol and water, and dried under vacuum. 20 mg of the obtained polyethylene glycol-modified nanoparticles were dispersed in 25 mL of ethanol, and 15 mg of protoporphyrin IX was added. The mixture was stirred at room temperature in the dark for 12 h. After centrifugation at 10,000 rpm for 5 min and washing twice with ethanol, an acid-responsive bivalent iron nanoreactor was obtained.

[0035] Example 2: Structure and acid-responsive performance of the acid-responsive dual-valent iron nanoreactor obtained in Example 1 of this invention. (1) Structural characterization methods The hydration size and polydispersity index of silica nanospheres and DHU-FS were determined by dynamic light scattering. The particle morphology was observed using scanning electron microscopy and transmission electron microscopy. The spatial distribution of O, Si, and Fe was analyzed using high-angle annular dark-field scanning transmission electron microscopy and energy dispersive spectroscopy (EDS). The pore structure was determined using nitrogen adsorption-desorption experiments. Specific surface area was calculated using the BET method, and pore size distribution and pore volume were calculated using the BJH method. Fourier transform infrared spectroscopy was used to analyze polyethylene glycol modification, and UV-Vis absorption spectroscopy was used to analyze protoporphyrin IX loading.

[0036] X-ray photoelectron spectroscopy (XPS) was used to analyze the valence state of Fe. Charge correction was performed using the C 1s peak at 284.8 eV. High-resolution 2p spectra of Fe were acquired in the range of 700–740 eV, and peak shapes were fitted using Shirley background and GL(12.5) mixed peaks. The energy interval between the 2p¹ / ² and 2p³ / ² peaks of the same valence state was fixed at 13.1 eV, the area ratio was fixed at 0.518, and the full width at half maximum (FWHM) of the main peak was limited to 2.28–2.60 eV. Fe was calculated using the peak areas of Fe 2p³ / ² at 710.64 eV and 712.49 eV. 2+ and Fe 3+ The relative content of satellite peaks is not included in the quantification. The encapsulation efficiency of protoporphyrin IX is calculated as "(mass of protoporphyrin IX fed - mass of free protoporphyrin IX in supernatant and washing liquid) / mass of protoporphyrin IX fed × 100%", and the mass of free protoporphyrin IX is obtained from the quantification results of UV-Vis absorption.

[0037] (2) Structural characterization results The results are as follows Figure 2 As shown, in section a, the silica template is a relatively uniformly dispersed spherical particle; section b shows the hydrothermal dissolution-regeneration process using silica as a sacrificial template; section c shows that DHU-FS has a clearly defined hollow spherical structure; section d shows that O, Si, and Fe are relatively uniformly distributed in the particles, with no obvious large-sized iron aggregates observed; section e shows Fe... 2+ and Fe 3+ The iron species coexisted, with relative contents of 44.17% and 55.83%, respectively. The uniform Fe element distribution, mixed valence state iron signals, and the time-dependent destruction of the framework structure under acidic conditions mutually corroborate each other, supporting the strong correlation between iron species and the reconstructed silicon-oxygen network, rather than their existence primarily as large-sized free iron particles. f shows the polyethylene glycol-related -CH2- stretching vibration peak, supporting successful surface modification. The zeta potential changed from -8.49 mV to -5.76 mV before and after polyethylene glycol modification, further supporting the alteration of the particle surface chemical environment. g shows the Soret absorption band of protoporphyrin IX, supporting its loading into nanoparticles.

[0038] The obtained DHU-FS had an average hydrated particle size of 202.52 nm and a polydispersity index of 0.094, while the BJH had an average mesopore size of 9.551 nm and a pore volume of 0.435 cm³. 3 ·g -1 The specific surface area of ​​BET is 65.042 m². 2 ·g -1 The encapsulation efficiency of protoporphyrin IX was 52.52%. These results indicate that the prepared particles possess a bivalent iron framework, a hollow mesoporous structure, a polyethylene glycol surface layer, and protoporphyrin IX loading.

[0039] (3) Acid-responsive degradation and release test methods 0.5 mL of DHU-FSPP dispersion, concentration 4 mg·mL -1 Add the solids to PBS at pH 7.4, 6.5, or 5.5 respectively, and incubate with shaking at 37 °C. Take samples at 6 h, 12 h, and 60 h, centrifuge at 10,000 rpm for 5 min, redisperse the solids in a small amount of ethanol, and add 20 μL to a copper grid for transmission electron microscopy observation.

[0040] In the iron release assay, 4 mg of DHU-FSPP was dispersed in 10 mL of PBS at the corresponding pH, placed in a dialysis bag with a molecular weight cutoff of 3500 Da, and then immersed in 30 mL of PBS at the same pH. The mixture was continuously shaken at 37 °C and 100 rpm. At 0, 2, 4, 6, 12, and 24 h, 3 mL of the external release solution was collected for inductively coupled plasma atomic emission spectrometry (ICP-AES). Immediately afterward, 3 mL of preheated fresh PBS was added, and the cumulative iron release rate was calculated after volume correction. The release of protoporphyrin IX was determined using UV-Vis absorption spectroscopy and a protoporphyrin IX standard curve.

[0041] (4) Acid-triggered local coordination test method and results 0.5 mg DHU-FSPP was dispersed in pH 5.5 buffer and incubated for 24 h. The degradation products were collected and analyzed using transmission electron microscopy, UV-Vis absorption spectroscopy, fluorescence spectroscopy, Raman spectroscopy, and N 1s high-resolution X-ray photoelectron spectroscopy. Separately, 5 mg of protoporphyrin IX and 10 mg of FeCl3 were added to 5 mL of methanol and stirred at 60 °C for 5 h under nitrogen protection to prepare independent Fe-protoporphyrin IX samples as controls.

[0042] The results are as follows Figure 3 As shown in Figure a, DHU-FSPP maintains a largely hollow spherical structure at pH 7.4, while at pH 6.5 or 5.5, the shell loosens, the structure breaks down, and further collapses over time. Figures b and c show that both iron and protoporphyrin IX are released in a pH-dependent manner: at 24 h, the release of both is significantly inhibited at pH 7.4; at pH 5.5–6.5, the cumulative release rate of Fe is approximately 30%–47%, and the cumulative release rate of protoporphyrin IX is approximately 33%–43%. These results indicate that, compared to neutral conditions, weakly acidic conditions can simultaneously promote the release of framework-derived iron species and protoporphyrin IX within the same time window, but they do not necessarily have the same release rate.

[0043] Image d shows the emergence of newly formed small particles of approximately 40 nm after acid treatment, with morphology similar to that of independently prepared Fe-protoporphyrin IX samples. Images e and f show a decrease in the absorption characteristics of PpIX accompanied by fluorescence quenching, indicating changes in its electronic structure and aggregation state. The changes in the Raman vibration of the porphyrin ring shown in image g and the changes in the N 1s binding energy shown in image h further indicate an alteration in the electronic environment of the internal pyrrole nitrogen. The morphology, absorption, fluorescence, Raman, and N 1s XPS results form a complementary chain of evidence, collectively supporting the formation of a Fe-protoporphyrin IX-like coordination nanostructure by acid-triggered release of the component. In this embodiment, the term "like coordination structure" is used to describe the product, rather than limiting it to a pure compound with a single composition or a defined iron valence state.

[0044] Example 3: Fenton activity and photothermal properties (1) Fenton activity test method Fenton or Fenton-like activity was evaluated using methylene blue bleaching. A final concentration of 5 μg / mL was added to a 2 mL reaction system. -1 Methylene blue, 2.5 mM hydrogen peroxide, and DHU-FSPP were used to make the final concentrations of DHU-FSPP 10, 25, 50, 100, or 200 μg·mL, respectively. -1 The absorbance at 664 nm was measured after sonication for 10 min. In the pH-dependent test, 400 μg of DHU-FSPP was incubated with shaking in PBS at pH 5.5, 6.5, or 7.4 for 24 h, and then the material concentration was adjusted to 200 μg / mL. -1 The determination was performed. Independently prepared Fe-protoporphyrin IX samples were compared with Fe... 2+ The solutions were compared under the same conditions of total iron concentration, hydrogen peroxide concentration, and pH.

[0045] Radical capture was performed using 5,5-dimethyl-1-pyrrolline-N-oxide, followed by electron spin resonance assays. The total reaction volume was 50 μL, with a final pre-incubation concentration of 500 μg·mL for DHU-FSPP. -1 The final concentration of hydrogen peroxide was 1 mM. 5 μL of 1 M capture agent stock solution was added to make the final concentration 100 mM. After mixing, the mixture was pre-reacted for 8 min before the electron spin resonance signal was collected.

[0046] (2) Photothermal and photothermal enhanced Fenton test methods DHU-FSPP pre-incubated under different pH conditions was irradiated with a 658 nm laser for 10 min, and temperature changes were recorded using an infrared thermal imager. The effects of material concentration, laser power density, and repeated heating-cooling cycles on photothermal performance were investigated. The photothermal conversion efficiency was calculated based on the heating and cooling curves. Using 3,3′,5,5′-tetramethylbenzidine as a chromogenic substrate, DHU-FSPP, hydrogen peroxide, and tetramethylbenzidine were mixed and reacted with or without 658 nm illumination. The promoting effect of photothermal heating on the iron-mediated Fenton reaction was evaluated based on the absorption signal of oxidized tetramethylbenzidine.

[0047] (3) Test results like Figure 4 As shown in the figure; a to c show that methylene blue absorption decreases significantly when only DHU-FSPP and hydrogen peroxide are present, and the degree of fading increases with decreasing pH and increasing material concentration; d shows the electron spin resonance signal related to hydroxyl radicals generated in the complete reaction system. e and f show that, at the same total iron concentration, the methylene blue fading and hydroxyl radical generation induced by the independently prepared Fe-protoporphyrin IX sample are weaker than those induced by Fe. 2+ This indicates that Fe 2+ Enriched species are the main source of Fenton activity.

[0048] g shows that the Fe-protoporphyrin IX sample exhibits a concentration-dependent temperature increase under 658 nm illumination; h shows that the temperature increase of DHU-FSPP after incubation under acidic conditions is higher than that under pH 7.4 conditions; i and j show that the temperature increase increases with increasing light power density and material concentration, respectively; k shows that the material has repetitive heating-cooling stability, and the calculated photothermal conversion efficiency is 23.15%. l shows that 658 nm illumination further enhances the absorption signal of oxidized tetramethylbenzidine, proving that photothermal heating can promote iron-mediated Fenton or Fenton-like reactions.

[0049] The above comparison results indicate that the iron species in this system have functional specialization: Fe 2+ The enriched species primarily provide Fenton activity, while the Fe-protoporphyrin IX-like structure formed after acid triggering mainly provides the 658 nm photothermal response. The mild temperature rise caused by light irradiation further promotes the iron-mediated oxidation reaction. Therefore, the enhancement effect comes from a continuous process of acid-responsive release, local coordination, and photothermal promotion of the Fenton reaction, rather than using the pre-prepared Fe-protoporphyrin IX itself as the main Fenton catalyst.

[0050] Example 4 Biological Effects (1) Cell uptake and cell damage assay methods DHU-FSPP and Cy5.5 were stirred at room temperature in the dark for 12 h, centrifuged, and washed three times with deionized water to remove free dye. Cy5.5-labeled DHU-FSPP was incubated with 4T1 cells. Acidic endocytic or lysosomal compartments were labeled with Lyso Tracker, and cell nuclei were labeled with DAPI. Material uptake and intracellular distribution were observed using confocal microscopy. Cell viability was determined using the CCK-8 assay; live / dead staining was performed using Calcein-AM and propidium iodide.

[0051] In the cell ultrathin section assay, 4T1 cells or L929 cells were mixed with a final concentration of 50 μg·mL⁻¹. -1 The nanomaterials were incubated at 37 °C for 6 h, and the illumination group used 658 nm and 0.5 W·cm⁻¹ light. -2 Laser irradiation was performed; followed by fixation with 2.5% glutaraldehyde at 4°C for 4 h, and then post-fixation with 1% osmium tetroxide for 2 h. After dehydration with graded ethanol, resin embedding, and ultrathin sectioning at 60–70 nm, the samples were observed under a transmission electron microscope.

[0052] (2) Measurement of oxidative stress and ferroptosis-related indicators Intracellular total reactive oxygen species (ROS) levels were assessed using the DCFH-DA fluorescent probe. Mitochondrial membrane potential changes were evaluated using JC-1 staining. GSH and GSSG were measured using kits, and the GSH / GSSG ratio was calculated. Antioxidant defense and ferroptosis-related changes were evaluated using GPX4 immunofluorescence and Western blotting of SLC7A11, GPX4, FTH1, and HSP70 proteins. Each quantitative assay included at least three independent biological replicates.

[0053] (3) Animal testing methods 50 μL of a concentration of 1×10 6 pcs·mL -1 4T1 cell suspension was inoculated into the right mammary fat pad of 6-8 week old female BALB / c mice until the tumor volume reached approximately 100 mm. 3 Animals were randomly divided into a control group, a laser group, a DHU-FSP group, a DHU-FSPP group, and a DHU-FSPP combined with laser group, with three animals in each group. The corresponding nanoparticles were dispersed in sterile PBS to form an aqueous dispersion before use. The nanoparticle-treated groups were treated with a total nanoparticle mass of 20 mg / kg. -1 The drug was administered via tail vein once every 2 days for a total of 14 times over 4 weeks; the control and laser groups received an equal volume of sterile PBS via tail vein. The light irradiation group received 658 nm, 0.5 W·cm² treatment 12 hours after each administration. -2 The tumor was irradiated with laser for 10 minutes. Mouse weight and tumor volume were recorded, with tumor volume expressed as V = length × width. 2 / 2 calculation; after the experiment, the tumor was weighed, and hematological, liver and kidney function, hematoxylin-eosin staining of major organs, and tumor tissue protein expression and histological indicators were analyzed. The animal experiment was approved by the Animal Ethics Committee of Shanghai Tenth People's Hospital, approval number SHDSYY-2024-4343-3.

[0054] (4) Test results The results are as follows Figure 5-7 As shown; where Figure 5 Figures a and b show that Cy5.5-labeled DHU-FSPP can be taken up by 4T1 cells and partially overlaps with acidic endocytic or lysosomal compartments; the Pearson correlation coefficient is 0.23, indicating that only some material-related signals co-localize with the acidic compartment, while the remaining signals are distributed in other intracellular regions. Figure c shows that nanomaterials and particulate-like transformation products are visible in 4T1 cells, while the corresponding changes are weaker in L929 cells. This difference is limited to the cells and observation conditions used in this example. Figures d and e show that the proportion of dead cells is highest in the DHU-FSPP combined with 658 nm light irradiation group, which is higher than the groups using only materials or only light irradiation, indicating that light irradiation can enhance material-induced cell damage.

[0055] like Figure 6 As shown, Figure 6 Image a shows intracellular reactive oxygen species (ROS) fluorescence; image b shows JC-1 mitochondrial membrane potential staining; images c and d show GPX4 immunofluorescence and quantification results, respectively; image e shows the intracellular GSH / GSSG ratio. DHU-FSPP combined with light treatment increased intracellular ROS signal, decreased mitochondrial membrane potential and GSH / GSSG ratio, and reduced GPX4 signal. Combined with decreased SLC7A11 and GPX4 protein expression, these changes indicate that the combined treatment weakened cellular antioxidant defense and caused ferroptosis-related damage. Changes in ROS, mitochondrial membrane potential, GSH / GSSG, and GPX4 collectively support this mechanism, but these indicators are not the sole specific criteria for ferroptosis. Therefore, this embodiment describes the results as "ferroptosis-related changes."

[0056] Figure 7Figure a shows that tumor-bearing mice were treated according to the established drug administration and light irradiation protocol; figure b shows that no significant weight loss occurred in any group during the experiment; figure c shows that the local tumor temperature in the DHU-FSPP combined with light irradiation group increased from 36.5 °C to 43.5 °C during irradiation; figure d shows that this group had the lowest ex vivo tumor volume and mass, with a reported tumor growth inhibition rate of 72.5%. Compared with the control group, the laser group, and the material group without combined light irradiation, the DHU-FSPP combined with light irradiation group showed stronger tumor growth inhibition, supporting the enhancing effect of local photothermal heating on iron-mediated oxidative damage; figure e shows that the expression of SLC7A11 and GPX4 in the tumor tissue of the combined treatment group was reduced; figure f shows that the tumor tissue necrosis and structural disorder were aggravated in this group, GPX4 positive staining was reduced, and TUNEL positive signal was increased. At the end of the experiment, no significant abnormalities were found in hematological parameters, ALT, AST, ALP, BUN, and creatinine in any group, and no significant tissue damage was found in hematoxylin-eosin staining of the heart, liver, spleen, lungs, and kidneys.

[0057] The above results indicate that, in this example, 20 mg·kg -1 Under the given dosage, 4-week observation period, and 3 animals per group, the material exhibited acceptable short-term tolerability; this conclusion is not extrapolated to higher doses or longer observation periods. Combined with the cellular and animal results, this embodiment supports the use of the described nanoreactor for the preparation of drugs for chemokinetic and photothermal-enhanced tumor therapy.

[0058] The nanoreactor described in this invention can be prepared by sol-gel, hydrothermal dissolution-regeneration, silanization modification and physical loading processes. The raw materials are readily available, the preparation process is reproducible, and it can be used for further scale-up and formulation research, thus having significant industrial applicability.

[0059] The above description is not limited to the examples above. Technical features not described in this invention can be implemented by or using existing technology, and will not be repeated here. The above embodiments are only used to illustrate the technical solutions of this invention and are not intended to limit this invention. Any changes, modifications, additions or substitutions made by those skilled in the art within the scope of this invention do not depart from the spirit of this invention and should also fall within the scope of protection of the claims of this invention.

Claims

1. An acid-responsive dual-valent iron nanoreactor, characterized in that, It includes Fe-doped hollow mesoporous silica nanoparticles, a polyethylene glycol layer disposed on the surface of the nanoparticles, and protoporphyrin IX supported in the hollow cavity and / or mesopores; the Fe is Fe 2+ and Fe 3+ They coexist and form part of the nanoparticle framework through Si-O-Fe bonds; the nanoreactor undergoes framework degradation under pH 5.5–6.5 conditions and co-releases iron species and protoporphyrin IX to form a Fe-protoporphyrin IX-like coordination structure.

2. The acid-responsive divalent iron nanoreactor according to claim 1, characterized in that, The Fe-doped hollow mesoporous silica nanoparticles have an average hydrated particle size of 202.52 nm, an average mesopore size of 9.551 nm, and a specific surface area of ​​65.042 m². 2 ·g -1 The pore volume is 0.435 cm³. 3 ·g -1 The Fe 2+ and Fe 3+ The relative contents were 44.17% and 55.83%, respectively, and the encapsulation efficiency of the protoporphyrin IX was 52.52%.

3. A method for preparing an acid-responsive divalent iron nanoreactor as described in claim 1 or 2, characterized in that, Includes the following steps: Using silica nanospheres as sacrificial templates, a hydrothermal dissolution-regeneration reaction was carried out in the presence of iron acetylacetone and urea to obtain Fe-doped hollow mesoporous silica nanoparticles; the nanoparticles were then surface-modified with methoxy polyethylene glycol silane; and the surface-modified nanoparticles were incubated with protoporphyrin IX in ethanol in the dark to load protoporphyrin IX into the hollow cavity and / or mesopores.

4. The preparation method according to claim 3, characterized in that, The hydrothermal dissolution-regeneration reaction includes: dispersing 12.5 mg of silica nanospheres in 3.75 mL of deionized water, adding 88 mg of ferric acetylacetone, 1200 mg of urea and 2.5 mL of ethanol, and reacting at 200 °C for 24 h.

5. The preparation method according to claim 3, characterized in that, The surface modification includes reacting 80 mg of Fe-doped hollow mesoporous silica nanoparticles with 50 mg of methoxy polyethylene glycol silane in anhydrous ethanol at 78 °C for 24 h; the protoporphyrin IX loading includes stirring 20 mg of surface-modified nanoparticles with 15 mg of protoporphyrin IX in 25 mL of ethanol in the dark for 12 h.

6. A pharmaceutical composition, characterized in that, The invention includes the acid-responsive bivalent iron nanoreactor as described in claim 1 or 2, and a pharmaceutically acceptable aqueous carrier, wherein the aqueous carrier is a sterile phosphate buffer or physiological saline.

7. The use of the acid-responsive bivalent iron nanoreactor of claim 1 or 2 in the preparation of medicaments for tumor chemokinetics and photothermal enhancement therapy, wherein the medicaments are adapted for use under 658 nm illumination.